Financializing urban infrastructure? The speculative state-spaces of 'public-public partnerships' in Jakarta. (March 2023) - Anguelov, Dimitar
Mega city-regions in the global South facing challenges posed by rapid urbanization have turned to infrastructural solutions, steeped in speculative 'global-city' imaginaries and national developmental aspirations, in order to unclog catch-up growth. This infrastructural imperative for growth reflects a broader infrastructure fix, as creditor states and development banks with geopolitical and geoeconomic interests advance competing market-based and state-led models to finance and develop infrastructure. In Jakarta, Indonesia, I examine the coming together of these models as they articulate with the political-economies of city and state, and their path-dependent restructuring following the 1997 Asian Financial Crisis. In Jakarta's speculative state-space political interests and developmental objectives of state and city governments are entangled with the capital accumulation strategies of State-Owned Enterprises. With a number of rail transit projects in the city-region driving a boom in Transit-Oriented Development, State-Owned Enterprises speculate on market conditions and the 'world-class city' dreams of middle-class residents to leverage their property assets. This financial speculation is equally premised on political speculation around the planning and execution of infrastructure projects, framed by the developmental politics of affordability and accessibility to the city. I examine how these strategies, practices and tensions come together to produce innovative governance arrangements in the provision and management of transport and housing through Public-Public Partnerships .